A prospective study of tea and coffee intake and risk of glioma - Cote, David J. (Int J Cancer, 2019)
Tea and coffee have antioxidant and neuroprotective effects. Observational studies suggest that tea and coffee intake may reduce cancer risk, but data on glioma risk are inconclusive. We evaluated the association between tea, coffee and caffeine intake and glioma risk in the female Nurses’ Health Study (NHS) and Nurses’ Health Study II (NHSII) and the male Health Professionals Follow-Up Study (HPFS). Cumulative intake was derived from validated quadrennial food frequency questionnaires. Glioma cases were confirmed by medical record review. Multivariable-adjusted hazard ratios of glioma by beverage intake category were estimated using Cox proportional hazards models. We documented 554 incident cases of glioma (256 in NHS, 87 in NHSII and 211 in HPFS). Compared to <1 cup/week, higher tea consumption was borderline inversely associated with glioma risk in pooled cohorts (hazard ratio [HR] = 0.73, 95% confidence interval [CI]: 0.49–1.10 for >2 cups/day, p-trend = 0.05), but not in women (HR = 0.74, 95% CI: 0.47–1.18 for >2 cups/day, p-trend = 0.11) or men (HR = 0.70, 95% CI: 0.30–1.60 for >2 cups/day, p-trend = 0.30) separately. Overall, we observed no significant associations between caffeinated, decaffeinated or total coffee intake and glioma risk. There were no material differences in the results with baseline values, 8-year lagged responses, or when limited to glioblastoma (n = 362). In three large prospective cohort studies, tea intake was borderline inversely associated with glioma risk. No significant associations were observed for coffee intake and glioma risk. These results merit further exploration in prospective studies.